کانزاکاری و سەرچاوەکانی بەدەستهێنانی کانزا لە کوردستانی دێریندا - داغي, رافدة عبدالله عبدالصمد القره; محمد, وفاء طاهر (Sulaimani Journal for Humanities, 2022)
Although southern Mesopotamia is regarded as the cradle of civilization, because the most ancient civilization regarded here, but according to the environment the country is poor in row materials like metals, wood and stones, but Sumerians, Akkadian and Babylonians worked hard to obtain these materials this pushed them to bring it from upper Mesopotamia in Kurdistan and the Zagros-Taurus ranges to build their civilization. It seems that the land of Kurdistan was the main source of these materials or as a path leads and links the trade of metals between its main sources and Mesopotamia. This research works in that frame and it deals with the sources of metals, its places, the way they used and the sorts of metals according to archeological and cuneiform records.